2005
DOI: 10.1016/j.jtcvs.2005.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery after percutaneous transmitral commissurotomy: Operative versus echocardiographic findings, mechanisms of complications, and outcomes

Abstract: Acute mitral regurgitation and cardiac tamponade were the causes of emergency surgery after balloon valvotomy. Transthoracic echocardiography underestimated the severity of valve pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 13 publications
4
20
0
1
Order By: Relevance
“…24 Our results showed that 20(16.12%) got mild MR, 2(1.6%) had moderate MR and 4(2.173%) severe MR and these results coincide with other studies. Significant MR is defined as MR of ≥2/4 grade.…”
Section: Discussionsupporting
confidence: 92%
“…24 Our results showed that 20(16.12%) got mild MR, 2(1.6%) had moderate MR and 4(2.173%) severe MR and these results coincide with other studies. Significant MR is defined as MR of ≥2/4 grade.…”
Section: Discussionsupporting
confidence: 92%
“…This increases the chances of a high septal puncture with attendant risk of haemopericardium and cardiac tamponade. Transoesophageal echocardiography (TOE) can be helpful in avoiding this complication 13. A very large right atrium may not allow adequate tenting of the interatrial septum for the needle to enter the LA.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,5,6] The extensively fused and thickened subvalvar structures and calcium in the commissures are unyielding sites of greater resistance leading to persistent MS. The PAH of the unrelieved MS is acutely worsened by severe MR.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with severe MR as defined by a Doppler color flow mapping of regurgitant jet-to-left atrial (LA) area ratio of 76-100% usually require emergency MVR. [5] Acute severe (gradient 24/13 mmHg), MV area of 0.6 cm 2 , mild MR, large LA with no clots, mild tricuspid regurgitation (TR), moderate pulmonary arterial hypertension (PAH), right ventricular (RV) internal diameter (ID) 12 mm and left ventricular (LV) ejection fraction (EF) 52%. The MV lateral commissure was fused and the patient was taken up for BMV.…”
Section: Introductionmentioning
confidence: 99%